STUDENTS’ PERCEPTION TOWARDS THE ROLE OF ICE BREAKING ACTIVITIES IN LEARNING ENGLISH AT SENIOR HIGH SCHOOL - Naila Al Ghifarah; Ririn Pusparini (Journal of English Language Teaching and Literature (JELTL), 2023)
One of many factors that can influence students' feelings while learning English is a teacher's method or style of instruction that is not precise or monotonous. A fun and attractive learning environment can help students focus better and become more motivated to learn. Applying learning strategies suitable to students' conditions is one solution for increasing students'' motivation. For instance, the "ice-breaking" activity. Moreover, this research uses a qualitative approach to achieve the purposes of the research. The participants of this study were 30 students in a particular Islamic senior high school in Sidoarjo. This study used questionnaire, interview, and observation as research instruments. The study's findings indicate that students have a positive perception towards the role of ice breaking activities in learning English at senior high school. Ice-breaking is an effective strategy for increasing student motivation. Moreover, it has the potential to encourage students to learn. So that the classroom atmosphere becomes enjoyable and students' understanding of the subject matter improves.